Water Management for Climate Smart Agriculture (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Global climate change has resulted in significant changes in local weather conditions in many countries. Changes in rainfall and temperature threaten agricultural production and increase the vulnerability of individuals who are dependent on agriculture. In particular, water shortages in arid and semi-arid regions will become more prominent. In such regions, irregularly distributed rainfall will result in increased droughts as well as extreme rainfall events. Climate-smart agriculture (CSA) is an approach that aims to transform and reorient agricultural systems to adapt to the effects of climate change.The present reprint, “Water Management for Climate-Smart Agriculture”, gathers the latest knowledge on water management practices to guide and support stakeholders, researchers, and students in adopting CSA in arid and semiarid regions to achieve sustainable and resilient agricultural systems. This Special Issue consists of a range of topics, e.g., rainwater harvesting, drought, efficient farming practices, irrigation, and groundwater recharge, and presents real-world case studies, practical examples, and applicable recommendations to be considered and applied. We hope that the knowledge provided in this reprint can be of help for the adoption of climate-smart water management practices not only in Iraq but also in other arid and semi-arid regions.